Can tip-apex distance and calcar reference tip-apex distance predict lag screw cut-out in elderly patients with trochanteric femoral fractures treated with gamma3 nails - Iamsum-Ang, Chonlathan; Chensupakarn, Chinakrit; Wannachotphawet, Supinya (International Journal of Research in Orthopaedics, 2024)
Background: The most common complication of cephalomedullary nail fixation for femoral fractures is lag screw cut-out. The significance of the tip-apex distance (TAD) in predicting lag screw cut-out is still debated. There has been no study conducted on the calcar reference tip-apex distance (CalTAD) regarding its impact on lag screw cut-out. To compare the average TAD and CalTAD between groups with and without lag screw cut-out and to determine the TAD and CalTAD values associated with the highest risk of lag screw cut-out. Methods: This was a prognostic prediction study utilizing a retrospective cohort of 756 patients with trochanteric femoral fractures treated with Gamma3 nails. This study compared the differences in TAD and CalTAD values between the two groups. Results: The group without lag screw cut-out had lower TAD and CalTAD values compared to the group with lag screw cut-out (TAD; 20.3±5.3 mm vs. 22.1±5.7 mm; p=0.044); (CalTAD 22.3±4.4 mm vs. 25.2±5.3 mm; p<0.001). The cutoff points of TAD >23 mm and CalTAD >25 mm were associated with the highest risk of lag screw cut-out (TAD: OR, 2.91; 95% CI, 1.47-5.77; p=0.002); (CalTAD: OR, 3.43; 95% CI, 1.73-6.80; p<0.001). Conclusions: The lag screw cut-out group had higher TAD and CalTAD values. TAD values greater than 23 mm and CalTAD values greater than 25 mm were associated with the highest risk of lag screw cut-out.